Adaptive management: Promises and pitfalls - McLain, Rebecca J.; Lee, Robert G. (Environmental Management, 1996)
Proponents of the scientific adaptive management approach argue that it increases knowledge acquisition rates, enhances information flow among policy actors, and provides opportunities for creating shared understandings. However, evidence from efforts to implement the approach in New Brunswick, British Columbia, Canada, and the Columbia River Basin indicates that these promises have not been met. The data show that scientific adaptive management relies excessively on the use of linear systems models, discounts nonscientific forms of knowledge, and pays inadequate attention to policy processes that promote the development of shared understandings among diverse stakeholders. To be effective, new adaptive management efforts will need to incorporate knowledge from multiple sources, make use of multiple systems models, and support new forms of cooperation among stakeholders.

Appraising Adaptive Management - Lee, Kai (Conservation Ecology, 1999)
Lee, K. N. 1999. Appraising adaptive management. Conservation Ecology 3(2): 3. https://doi.org/10.5751/ES-00131-030203

Adaptive Management - Bormann, B.T.; Martin, J.R.; Wagner, F.H.; Wood, G.W.; Alegria, J. (Ecological stewardship: a common reference for ecosystem management, 1999)
Wagner
Keywords: Conservation of natural resources; Ecology; Ecosystem management; Ecosystem management - United States; Environmental Science; Environmental management; Wildlife

Compass and Gyroscope: Integrating Science and Politics in the Environment - Lee, Kai N. (Island Press, 1993)
In this original and far-reaching synthesis, Kai N. Lee explains that together science and politics can lead the waytoward the sustainable management of the world’s resources. Rigorous science can act as our compass, pointingus toward greater and more useful knowledge (adaptive management), and practical politics can serve as our gyroscope, keeping usbalanced between competing interest groups. Unlike some approaches to sustainable development, Compass and Gyroscope is refreshingly grounded in the realworld. Lee explains that sustainability cannot occur overnight, we have neither an adequate base of knowledgenor a reliable means of properly implementing and executing management plans. "Sustainable development is not a goal, not a condition likely to be attained on earth as we know it. Rather it is more like freedom or justice,a direction in which we strive..." Using the Columbia River Basin in the Pacific Northwest as a case study, Lee examines the successes andfailures of past and present management. He describes what has been learned, and explains how that experiencecan be applied to environmental management generally. Throughout, the author delves deeply into the theoretical framework behind the real-world experience, exploring how theories of science, politics, and cognitive psychology can be integrated into environmental management.

Harnessing Complexity: Organizational Implications of a Scientific Frontier - Axelrod, Robert M.; Cohen, Michael D. (Free Press, 1999)
Recent advances in the study of complexity have given scientists profound new insights into how natural innovation occurs and how its power can be exploited. Now two pioneers in the field, Robert Axelrod and Michael D. Cohen, provide leaders in business and government with a guide to complexity that will help them make effective decisions in a world of rapid change. Building on evolutionary biology, computer science, and social design, Axelrod and Cohen have constructed a unique framework for improving the way people work together. Their approach to management is based on the concept of the Complex Adaptive System, which can describe everything from rain forests to the human gene pool, and from automated software agents to multinational companies. The authors' framework reveals three qualities that all kinds of managers must cultivate in their organization: "Variation" What is the best way to manage the development of software? Should the problem be broken up into small pieces for programmers working independently, thus enhancing variation, or should there be a centralized hierarchy of programmers ruled by a chain of command? The authors show how the decentralized creation of variation combined with the centralized maintenance of standards was the key to the success of the Linux "open source software" project, which brought together thousands of volunteers in cyberspace to produce an operating system that can outperform Microsoft's. "Interaction" Why did northern Italy prosper while southern Italy remained poor? Recognizing the internal interactions of a Complex Adaptive System -- be it a national region, a company, or a nonprofit group -- reveals vitalnetworks of trust. Axelrod and Cohen explain that in successful adaptive systems, rich networks of horizontal linkages foster cooperation and provide an advantage over other less cooperatively networked groups. In the case of Italy, voluntary associations created networks of trust in the Middle Ages that became northern Italy's critical advantage over the south. "Selection" Is a Pulitzer Prize better than a National Book Award? How can foundations and corporations design competitions that have a positive effect on the evolution of excellence? The authors' framework makes clear that the worst selection processes are mired in orthodox standards that have not adapted to a new environment. The best selection processes, on the other hand, are created and run by leaders who understand how the standards they use can transform their organization and its environment. This simple, paradigm-shifting analysis of how people work together will transform the way we think about getting things done in a group. "Harnessing Complexity" is the essential guide to creating wealth, power, and knowledge in the 21st century.
Keywords: Organizational Behavior

When Knowledge is Power: Three Models of Change in International Organizations - Haas, Ernst B. (University of California Press, 1991)
Do governments seeking to collaborate in such international organizations as the United Nations and the World Bank ever learn to improve the performance of those organizations? Can international organizations be improved by a deliberate institutional design that reflects lessons learned in peacekeeping, the protection of human rights, and environmentally sound economic development? In this incisive work, Ernst Haas examines these and other issues to delineate the conditions under which organizations change their methods for defining problems. Haas contends that international organizations change most effectively when they are able to redefine the causes underlying the problems to be addressed. He shows that such self-reflection is possible when the expert-generated knowledge about the problems can be made to mesh with the interests of hegemonic coalitions of member governments. But usually efforts to change organizations begin as adaptive practices that owe little to a systematic questioning of past behavior. Often organizations adapt and survive without fully satisfying most of their members, as has been the case with the United Nations since 1970. When Knowledge Is Power is a wide-ranging work that will elicit interest from political scientists, organization theorists, bureaucrats, and students of management and international administration.

Development as Process: Concepts and Methods for Working with Complexity - Mosse, David; Farrington, John; Rew, Alan (Routledge, 1998)
Process" approaches to economic and social development appear to be more flexible and offer greater prospects of success than traditional "project" methods. Development as Process addresses the questions raised by the different natures of the two approaches. The authors examine development projects through experience in water resources development in India and in organizational learning by a Bangladeshi NGO. Inter-agency contexts are examined in the setting of an aquaculture project in Bangladesh and in the setting of agriculture and natural resources development in Rajisthan, India. Finally, the role of process monitoring is explained in the context of policy reform, with illustrations from forestry in India and land reform in Russia.
Keywords: Demography; Economic Development; Sociology

Whose Reality Counts? Putting the First Last - Chambers, Robert (ITDG Publishing, 1997)
In this sequel to "Rural Development: Putting the last first" Robert Chambers argues that central issues in development have been overlooked, and that many past errors have flowed from domination by those with power.Development professionals now need new approaches and methods forinteracting, learning and knowing. Through analyzing experience - of past mistakes and myths, and of the continuing methodological revolution of PRA (participatory rural appraisal) - the author points towards solutions.In many countries, urban and rural people alike have shown an astonishing ability to express and analyze their local, complex and diverse realities which are often at odds with the top-down realities imposed by professionals. The author argues that personal, professional and institutional change is essential if the realities of the poor are to receive greater recognition. Self-critical awareness and changes in concepts, values, methods and behaviour must be developed to explore the new high ground of participation and empowerment."Whose Reality Counts?" presents a radical challenge to all concernedwith development, whether practitioners, researchers or policy-makers, in all organizations and disciplines, and at all levels from fieldworkers to the heads of agencies. With its thrust of putting the first last it presents a new, exciting and above all practical agenda for future development which cannot be ignored.